Phytochemical composition and antioxidant activity of three medicinal plants from southeastern Kazakhstan (International Journal of Biology and Chemistry, 2022)
Main results on study of phytochemical composition and antioxidant activity of three plants growing in southeastern part of Kazakhstan, namely A. schrenkiana, L. turkestanicus and C. tianschanica. Plant material was collected on flowering stage in July 2020. This study was carried out to evaluate the phytochemical constituents and antioxidant potential in order to validate the medicinal potential of these herbs. The antioxidant activity of alcoholic extracts was evaluated using 2,2 diphenyl-l-picrylhydrazyl (DPPH) assays. The total polyphenol and flavonoid content were determined according respectively to Spanos-Wrolstad and Zhishen method. The essential oil composition of samples was analyzed by gas chromatography (GC) (Agilent 7890A) coupled by flame ionization detector and mass spectrometry (Agilent 5975C) using capillary column (HP Innowax Capillary; 60.0 m×0.25 mm×0.25 µm). Phenols in A. schrenkiana (2.83 mg OE/g), in L. turkestanicus (2.86 mg OE/g), in C. tianschanica (16.08 mg OE/g). Flavonoids in C. tianschanica (21.79 mg RE/g), in L. turkestanicus (4.29 mg RE/g), in A. schrenkiana (3.8 mg RE/g). C. tianschanica (IC50 = 0.78 µg.mL) had greater antioxidant activity than A. schrenkiana (IC50 = 3.7 µg.mL) and L. turkestanicus (IC50 = 3.38 µg.mL). The components of the essential oil of A. schrenkiana revealed 13 types of chemical elements, of which the indicators of camphor (44.79%) and 1.8-cineole (29.05%) were high.